The occurrence and pathogenicity of Serratospiculum tendo (Nematoda: Diplotriaenoidea) in birds of prey from southern Italy. Issue 3 (16th March 2015) - Santoro, M.; D'Alessio, N.; Di Prisco, F.; Kinsella, J.M.; Barca, L.; Degli Uberti, B.; Restucci, B.; Martano, M.; Troisi, S.; Galiero, G.; Veneziano, V.
Abstract: The air sacs of free-ranging birds of prey ( n = 652) from southern Italy, including 11 species of Accipitriformes and six of Falconiforms, were examined for infections with Serratospiculum tendo (Nematoda: Diplotriaenoidea). Of the 17 species of birds examined, 25 of 31 (80.6%) peregrine falcons ( Falco peregrinus ) from Calabria Region and a single northern goshawk ( Accipiter gentilis ) from Campania Region were infected with S. tendo, suggesting a strong host specificity for the peregrine falcon. The northern goshawk and 18 of 25 infected peregrine falcons showed cachexia and all infected birds had bone fractures. At gross examination, air sacculitis and pneumonia were the most common lesions in infected birds. Microscopically, the air-sac walls showed thickening of the smooth muscle cells, resulting in a papillary appearance, along with hyperplasia of the mesothelium and epithelium, and foci of plasma cell infiltration and macrophages associated with several embryonated eggs and adult parasites. Extensive areas of inflammation were found in the lungs, characterized by lymphocytes, macrophages and fibroblasts surrounding embryonated eggs. The northern goshawk also had detachment of the dextral lung with several necrotic foci. In this case, the death of the bird was directly attributed to S. tendo infection. Lesions and pathological changes observed here suggest that S. tendo can cause disease.